Analisis Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Burger Bros Cabang Tebet - Enno Setiawan; Afghan Maulana Putra; Nana Permana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Consumer behavior is part of buying and selling activities that are complex and broad to be explored. Even so, the purchase decision is a consumer behavior that is based on the results of experience and evaluation of previous purchases. this behavior can also be influenced by how good the quality of a product is and also the price level which is the exchange rate of what is considered equivalent. Therefore, this study aims to examine how product quality and price factors influence purchasing decisions at Burger Bros Tebet branch, South Jakarta. This research is an associative research, and uses primary data obtained by documentation studies and questionnaires whose measurement uses a Likert differential scale. This quantitative research involved 100 respondents who were consumers of the product. The empirical data shows that product quality and price significantly influence purchasing decisions with a calculated F value of 219,647. While the resulting significance value is 0.000 ≤ 0.05. Thus, purchasing decisions are mediated by product quality accompanied by appropriate pricing.